2022
DOI: 10.3389/fnut.2022.929891
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leucine Supplementation on Sarcopenia-Related Measures in Older Adults: A Systematic Review and Meta-Analysis of 17 Randomized Controlled Trials

Abstract: BackgroundThe role of leucine in sarcopenia prevention remains unclear. We aimed to summarize the published data from randomized controlled trials (RCTs) to estimate the effect of leucine supplementation on sarcopenia-related measures in older adults.MethodsA systematic literature search was performed using the electronic databases PubMed, Embase, and Web of Science with restriction to randomized controlled trials design from January 1, 2009 to March 19, 2022. Sarcopenia-related measures included handgrip stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…Fifteen systematic reviews We found 13 systematic reviews wherein the authors explored nutritional interventions in elderly individuals. Four systematic reviews showed the beneficial effects of leucine supplementation [42][43][44][45]. Three systematic reviews demonstrated the effect of β-hydroxyβ-methylbutyrate (HMB) on muscle mass and strength [46][47][48].…”
Section: The Analysis Of Retrieved Articles 321 Sarcopenia and Nutritionmentioning
confidence: 99%
“…Fifteen systematic reviews We found 13 systematic reviews wherein the authors explored nutritional interventions in elderly individuals. Four systematic reviews showed the beneficial effects of leucine supplementation [42][43][44][45]. Three systematic reviews demonstrated the effect of β-hydroxyβ-methylbutyrate (HMB) on muscle mass and strength [46][47][48].…”
Section: The Analysis Of Retrieved Articles 321 Sarcopenia and Nutritionmentioning
confidence: 99%
“…A 2015 meta-analysis showed that protein fractional synthetic rate was increased in a leucine-supplemented group compared with a control group; however, no increases in lean body mass or leg lean mass were recorded 46 . A more recent meta-analysis published in 2022 of 17 RCTs consisting of 1418 participants also demonstrated that leucine-isolated supplementation does not significantly improve muscle mass or strength in older people 47 . However, those who took a leucine supplement including vitamin D showed an increase in handgrip strength and gait speed.…”
Section: Leucinementioning
confidence: 99%
“…The mechanisms behind the enhanced effect of cotreatment remain unclear. However, it has been hypothesized that both leucine and vitamin D both inhibit muscle atrophy–related transcription factors and stimulate the mTORc pathway 47 …”
Section: Leucinementioning
confidence: 99%
See 2 more Smart Citations